Design of detailed models for use in fast aeroelastic simulations of permanent-magnet direct-drive wind turbines - Ochs, David S. (Kansas State University, 2012)
This thesis presents the design of two models for permanent-magnet direct-drive wind turbines. The models are of a 10 kW and a 5 MW wind turbine, which are representative of residential scale and commercial scale turbines respectively. The models include aerodynamic and mechanical simulations through the FAST software, as well as concurrent electrical simulations through the SimPowerSystems toolbox for MATLAB/Simulink. The aim is to provide wind turbine designers and researchers with a comprehensive simulation tool that they can use to design and test many different aspects of a wind turbine. The particular novelty of these models is their high level of detail in electromechanical simulations. For each model, a generator speed controller was designed in a reference frame attached to the generator’s rotor, and was executed with a 3-phase active rectifier using space-vector pulse-width modulation. Also for each model, active and reactive power controllers were designed in a reference frame synchronous with the grid, and were executed with a 3-phase inverter using space-vector pulse-width modulation. Additionally, a blade pitch controller was designed for the 5 MW model. Validation of the models was carried out in the MATLAB/Simulink environment with satisfactory results.
Keywords: Wind turbines; Permanent-magnet synchronous generators; Active rectifiers; Inverters; Electrical Engineering (0544)